Gentle Ben - Morey, Walt.; Schoenherr, John (New York : Puffin Books, 1992)
Traces the friendship between a boy and a bear in the rugged Alaskan Territory.
"Ages 8-12"--Cover p. 4.
"First published ...1965."
Keywords: Kodiak bears -- Fiction; Brown bears -- Fiction; Bears -- Fiction